Analysis Of Factors That Influence Employee Job Satisfaction At PT. Rodateknindo purajaya Bengkulu - Aldi valentino; Ida Anggriani; M. Rahman Febliansah (Penerbit Jurnal Indonesia, 2024)
The purpose of this research is to determine the factors that influence employee job satisfaction at PT. Rodateknindo Purajaya Bengkulu. This type of research is a type of quantitative exlanatory.. The data collection method in this research used observation techniques and questionnaires, with a sample of 130 respondents. The results showed that multiple linear regression Y = 17.462 + 0.212 X1 + 0.071 X2 + 0.098 X3 + 0.068 Where the coefficient is positive, meaning that there is a positive or unidirectional relationship between the variables fulfilling needs (XI), differences (X2), achieving values ​​(X3), justice (X4b), organizational culture (X5) and job satisfaction (Y) at PT. Rodateknindo Purajaya Bengkulu. The results of the needs fulfillment test (XI) show tcount 4.647> ttable 1.656 and significance 0.008 <0.05, meaning that fulfillment of needs (XI) has a positive and significant effect on job satisfaction (Y) at PT. Rodateknindo Purajaya Bengkulu The results of the difference test (X2) show tcount 2.694> ttable 1.656 and significance 0.005 <0.05, meaning that the difference (X2) has a positive and significant effect on job satisfaction (Y) at PT. Rodateknindo Purajaya Bengkulu. The results of the value achievement test (X3) show tcount 2.870> ttable 1.656 and significance 0.000 <0.05, meaning that value achievement (X3) has a positive and significant effect on job satisfaction (Y) at PT. Rodateknindo Purajaya Bengkulu. The results of the justice test (X4) show that tcount is 3.657> ttable 1.656 and the significance is 0.000 <0.05, meaning that justice (X4) has a positive and significant effect on job satisfaction (Y) at PT. Rodateknindo Purajaya Bengkulu. The results of the organizational culture test (X5) show tcount 3,800> ttable 1,656 and significance 0.000 <0.05, meaning that organizational culture (X5) has a positive and significant effect on job satisfaction (Y) at PT. Rodateknindo Purajaya Bengkulu. The results of the Ftable value, namely 22.106 > 2.67, then it is concluded that accepting the hypothesis, meaning that there is a simultaneous influence between meeting needs (XI), differences (X2), achieving values ​​(X3), justice (X4b), organizational culture (X5) on job satisfaction (Y) at PT. Rodateknindo Purajaya Bengkulu.